Storage Studies on Seeds of Chir Pine (Pinus roxburghii Sargent) - JAGDISH GAUTAM; S.D. BHARDWAJ; PANKAJ PANWAR (Seed Research, 2026)
The freshly collected seeds of chir pine were put in storage for 20 months at room temperature, 5±1°C, 0±1°C and -5+1°C in polythene bags, canvas bags and glass jars to determine the seed longevity. The seeds stored at 5±1°C temperature in glass jars proved to be the best for maintaining 79.5 per cent germination up to 16 months. The seeds stored at -5±1°C temperature in canvas bags was least effective in prolonging seed germinability.